Understanding The "Gap" Phenomenon In Outsourced Development Projects, Including The Dimensions Of The Gap: A Research Study - Xiu, Liu; Ali, Dhakir Abbas (Journal of Neonatal Surgery, 2025)
The "gap" effect, which reduces stakeholder enjoyment, results quality, and overall project satisfaction in outsourced IS development projects. By delving into its vast scope, this exploratory research hopes to shed light on the many aspects of the outsourced IS development gap and its consequences for project management. Problems with outsourcing may lower project performance, despite the fact that it is often utilized by enterprises to save money and get access to specialized expertise. Common problems with outsourced IS projects are highlighted and examined in this research. These problems include misaligned expectations, difficulties with communication, and cultural differences. This study makes use of case studies, interviews, and industry reports to fully understand the complicated and diverse gap phenomena in different project settings. The communication gap has been investigated, which includes problems with the exchange of data and the degree to which the client and the outsourced provider are aware of one another. Many times, researchers may mention cultural differences when asked to explain why team members have different goals, expectations, and approaches to problems. To have a better understanding of how the expectations gap impacts project results and stakeholder satisfaction, it is necessary to examine discrepancies between actual and expected delivery. This study aims to shed light on these characteristics in the hopes of elucidating the gap phenomena and suggesting potential solutions. A more comprehensive strategy that incorporates more cultural knowledge, more effective communication tactics, and upfront and transparent expectations might be the key to closing the gap.